Market Behaviors and Economic Crisis: Insights from Financial Economics - Haris, Abdul (The Journal of Business and Management Research, 2024)
The research abstract encapsulates a comprehensive exploration of market behaviors during economic crises within financial economics. The study aims to elucidate the intricate dynamics of market behaviors amidst crises and their implications for theory and practice in financial economics. Employing a mixed-methods approach, the research integrates theoretical frameworks with empirical evidence to offer insights into the complexities of market dynamics. The study design thoroughly examines theoretical constructs and empirical investigations, drawing upon established frameworks such as the Efficient Market Hypothesis and behavioral finance theories. The research unravels the interplay between rational and irrational factors driving market outcomes during crises through empirical studies, including analysis of historical market data and examination of investor behavior. The findings underscore the need for a nuanced understanding of market behaviors, emphasizing the integration of rational and behavioral perspectives in financial economics theory and practice. The study's implications extend to policymakers, investors, and market participants, providing actionable insights to navigate turbulent economic environments effectively and foster stability in global financial markets.